Solubility Enhancement Technologies and Research Emerged - Patel, Arun (International Journal of Pharmaceutical & Biological Archive, 2017)
Solubility is the phenomenon of dissolution of solid in liquid phase to give a homogenous system.Solubility is one of the important parameter to achieve desired concentration of drug in systemiccirculation for pharmacological response to be shown. Some drugs pose challenging problems in theirpharmaceutical product development process because of their low solubility and dissolution rates. Poorlywater soluble drugs often require high doses and enhancement in solubility and dissolution rate in theirformulation development especially solid dosage forms such as tablets and capsules. Low aqueoussolubility is the major problem encountered with formulation development of new chemical entities. Anydrug to be absorbed must be present in the form of an aqueous solution at the site of absorption. Most ofdrugs weakly acidic and weakly basic with poor aqueous solubility. Several conventional methods andnew emerging technologies have been developed for the improvement of the solubility of poorly watersolubledrugs include micronization, chemical modification, pH adjustment, solid dispersion,nanosuspension, Superdisantigrant, liquisolid technique, complexation, coâ€solvency, micellarsolubilization, hydrotropic, salt formation etc. The purpose of this review article is to describe thetechniques of solubilizaton for the attainment of effective absorption and improved bioavailability.